A 3.4 - 6.2 GHz Continuously tunable electrostatic MEMS resonator with quality factor of 460-530 - Xiaoguang Liu; Katehi, L.P.B.; Chappell, W.J.; Peroulis, D. (2009 IEEE MTT-S International Microwave Symposium Digest, 2009)
In this paper we present the first MEMS electrostatically-tunable loaded-cavity resonator that simultaneously achieves a very high continuous tuning range of 6.2 GHz:3.4 GHz (1.8:1) and quality factor of 460-530 in a volume of 18 times 30 times 4 mm 3 including the actuation scheme and biasing lines. The operating principle relies on tuning the capacitance of the loaded-cavity by controlling the gap between an electrostatically-actuated membrane and the cavity post underneath it. Particular attention is paid on the fabrication of the tuning mechanism in order to avoid a) quality factor degradation due to the biasing lines and b) hysteresis and creep issues. A single-crystal silicon membrane coated with a thin gold layer is the key to the success of the design.